2019
DOI: 10.1111/dom.13724
|View full text |Cite
|
Sign up to set email alerts
|

Deintensification in older patients with type 2 diabetes: A systematic review of approaches, rates and outcomes

Abstract: Aim To assess deintensification approaches and rates and evaluate the harm and benefits of deintensification with antidiabetic medication and other therapies among older people (≥ 65 years) with type 2 diabetes with or without cardiometabolic conditions. Methods We identified relevant studies in a literature search of MEDLINE, Embase, Web of Science and Cochrane databases to 30 October 2018. Data were extracted on baseline characteristics, details on deintensification and outcomes, and was synthesized using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(76 citation statements)
references
References 53 publications
(143 reference statements)
2
66
0
8
Order By: Relevance
“…Figure 12.1 depicts an algorithm that can be used to simplify the insulin regimen (75). There are now multiple studies evaluating deintensification protocols that, in general, demonstrate that deintensification is safe and possibly beneficial for older adults (78). Table 12.2 provides examples of and rationale for situations where deintensification and/or insulin regimen simplification may be appropriate in older adults.…”
Section: Beyond Glycemic Controlmentioning
confidence: 99%
“…Figure 12.1 depicts an algorithm that can be used to simplify the insulin regimen (75). There are now multiple studies evaluating deintensification protocols that, in general, demonstrate that deintensification is safe and possibly beneficial for older adults (78). Table 12.2 provides examples of and rationale for situations where deintensification and/or insulin regimen simplification may be appropriate in older adults.…”
Section: Beyond Glycemic Controlmentioning
confidence: 99%
“…[7][8][9][10] To date, there is limited evidence regarding the benefits and risks of deprescribing in people with diabetes. [11][12][13] Potential overtreatment appears to be common among older people with diabetes, and deprescribing may be difficult to implement in practice. 12,[14][15][16] Clinical guidelines for the treatment of diabetes and cardiovascular risk factors focus more on intensification than on deintensification of medications.…”
mentioning
confidence: 99%
“…Some studies suggested the added value of de‐intensification that outweighs the harm, particularly in older patients. However, to date, there is no solid established strategies on how to implement antidiabetic therapy de‐intensification to prevent the harm of overtreatment 23,42 …”
Section: Discussionmentioning
confidence: 99%